Study of Localization Algorithms of RFID Tags in Closed Areas - PhD. Babadjanov Elmurod Satimbaevich.; Toliev Khurshid Ilhamovich; Abdijamalova Dilnoza Abdigafurovna (Zien Journals, 2023)
Nowadays, RFID technology is one of the most effective technologies used in identification. In addition to its role in identification efficiency and supply chain optimization, RFID technology is also widely used in the issue of accurate localization of objects in closed areas. With the help of RFID tags, devices can be identified in real time, data can be retrieved and stored remotely. Usually, RFID systems are used to search for moving objects in a certain area (indoors), control access, and monitor events. For example, the localization of RFID tags is one of the most important problems in tracking animals in farms, tracking assets in warehouses, and tracking patients in hospitals. Complex localization algorithms are the basis of this technological process. The article explores the algorithms used in the localization of RFID tags in closed areas through a careful study of principles, methodologies and existing applications
Keywords: through; localization; algorithms; technological